2013 annual report - Shortgrass Steppe Long Term Ecological Research (SGS-LTER), author (Colorado State University. Libraries, 2013)
We continue our research activities as described in our proposal and the IM supplement, as well as our efforts to decommission our site and the project. In 2013 our research has led to 28 reports in peer-reviewed journals (25 published, 1 in press and 2 submitted). Our scientists have also completed 7 book chapters. Thirteen abstracts have been provided for meetings of research societies. Two PhD and two MS students have completed their dissertations/theses. Our IM team continues to prepare our experimental datasets for delivery to the LTER Network as part of our decommissioning. To date 100 of 133 datasets have been curated and are available online. Included on this report are the details for research, IM, outreach and project management.
SGS LTER annual report 2013: DEB 102731
SGS-LTER 2013 annual report
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Keywords: shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland; grassland ecology; long term ecological research